AVANCES EN EL ESTUDIO DE LESIONES BUCALES EN PACIENTES HIV POSITIVOS /SIDA - Romero Rivas, Roberto (1999)
The geal of our research is that, Community knows the initial and advanced oral lesions in asymptomatic carriers and patients with HIV positive patient/AIDS, respectively with the purpose of preventing from contangion of Acquired Inmuno Deficiency Syndrome(AIDS). In order to accomplish this work, dependent variable "oral lesions" was contrasted with independent variable "positive HIV patients/AIDS". We studied 147 cases and evaluated 132. Aclinical, mycologic and histopathologic research was carried out in order to get a diagnosis of the positive HIV/AIDS associated oral lesions, we selected 116 positive HIV/AIDS cases and HIV-/normal, control cases (16 cases). Four groups of pateients were formed. The first group included candidiasic lesions, 93 cases, 70.45%, where observed they were associated to the four stages of AIDS, with the most prevalence in the Pseudomembranous Candidiasis (72 cases, 77.4%), which was confirmed by culture in Sabourau Agar and smear in cultures, GRAM staining, divided hifas and microsperes. In lingual candidiasis, were stated it could be related to AIDS in an asymptomatic person, it it's not demors trated by ene er two ELISA tests. The secend group was about viral lesions, 19 cases, 14.39%, with the most prevalence of simple Herpes (6 cases,50%), followed by accuminatum condyloma (3 cases,25%) and Pilous Leukoplaquia (3 cases,25%). We made labial herpes smears in studied cases, besides, RAIN coloration, where, in those tissues, strongly dyed-nucleus with presence of a big quantity of DNA were observed. Tetraploid nucleus that increases and multiplies number of cromosomes in an anormal way. In the third group, they were tumor lesions (sarcoma), in 4 cases (3.30%). In lthe initial, Kaposi Sarcoma was a violet stain present in oral mucosa. Sarcoma was a violet staint present in orald mucosa. Sarcomatic tumors are preferably on the palate. In palate biospy, we observed two cross sections, Mallory coloration, nucleus with a big íncrease of DNA, that, perhaps, coul come from AIDS virus comosomes and with atypical nucleus and vascular angiosarcomatous structures. In the group four, orald lesions HIV negative/AIDS were founs Some of them were candidiasic lesions caused by diabetes, profuse administration of antibiotics,etc.